Morphometric valley classification of the bed topography of the Northeast Greenland Ice Stream, downstream of the EastGRIP ice core site - Carter, Charlotte; Paxman, Guy J G; Franke, Steven; Jansen, Daniela; Eisen, Olaf (PANGAEA, 2025)
The Northeast Greenland Ice Stream (NEGIS) is an elongated feature extending ~600 km into the interior of the Greenland Ice Sheet. Here, we investigate detailed subglacial topography along the length of the NEGIS to ascertain the characteristics of the ice stream bed. The morphology of valley cross-sectional profiles was analysed utilising the workflow of Paxman (2023), which extracted valley profiles from 2018 and 2022 AWI radio echo sounding surveys, as well as a wider selection of Operation IceBridge survey lines within the study area. Morphometric indices relating to valley depth, top width, V-index and curvature ratio were calculated for each profile, in order to produce quantitative characteristic metrics.
Keywords: EastGRIP; geomorphometry; Northeast Greenland Ice Stream (NEGIS); radio echo sounding; topography